2011
DOI: 10.1136/jclinpath-2011-200008
|View full text |Cite
|
Sign up to set email alerts
|

The criminal justice system's considerations of so-called near-virtual autopsies: the East Midlands experience

Abstract: Here, the authors show that PMCT is good at providing accurate causes of death and that the interpretation of cases is not significantly altered by the absence of histology. The authors show that in straightforward trauma deaths such as road traffic incidents, there exists the potential for the replacement of the invasive PM by PMCT examination. However, as yet, PMCT cannot provide all of the information that is expected by the criminal justice system in complex forensic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…PMCT was better at detecting trauma and clinically significant soft-tissue haemorrhage, and autopsy was better at detecting pulmonary thromboembolism and respiratory disease. This outcome is consistent with previous reports,22, 23 and supports our belief that the new gold standard for post-mortem investigation is PMCT (with targeted coronary angiography) followed by autopsy.…”
Section: Discussionsupporting
confidence: 93%
“…PMCT was better at detecting trauma and clinically significant soft-tissue haemorrhage, and autopsy was better at detecting pulmonary thromboembolism and respiratory disease. This outcome is consistent with previous reports,22, 23 and supports our belief that the new gold standard for post-mortem investigation is PMCT (with targeted coronary angiography) followed by autopsy.…”
Section: Discussionsupporting
confidence: 93%
“…Only two of the three lesions described in the autopsy were detected by conventional imaging. Moreover, only the first method detailed the format and vitality of the edges of the lesions, consistent with related studies 11,12. The left scapular lesion was not detected by PMCT.…”
Section: Discussionsupporting
confidence: 88%
“…Computed tomography (CT) imaging has been used as an adjunct in post-mortem practice for over 27 years [1] and has reached a stage in its development in autopsy practice such that Jeffery et al [2] recently suggested that it should be used in all forensic death investigations [where ''forensic'' in the United Kingdom is confined to the investigation of suspicious or homicide death and does not include other medico-legal autopsies, many of which will be found to be natural causes (so called ''routine'' cases)]. Despite this, and the growing literature within this field, a significant obstacle in the acceptance and widespread introduction of so called ''near virtual'' or ''minimally invasive'' autopsies, relates to the diagnosis of cardiac death and the failure of current post-mortem imaging to yield detailed information concerning the coronary arteries.…”
Section: Introductionmentioning
confidence: 99%